Territories of Music - Nelson, Peter (Recherches sémiotiques / Semiotic Inquiry, 2017)
Music can be understood as a phenomenon that entwines sound and listening : sounds are not just there for the taking, they have to be identified – constructed even – in an interplay between the phenomenon of the sound and the phenomenon of the listening. This formulation goes to the heart of a contemporary ethos, which is an evening out of the hierarchies of the world in a way that places humans as no more than equal with other phenomena. Thus listening actually constitutes sound, in the sense that our activity of listening in the world negotiates a territory, where the negotiation has to deal with, rather than impose on the world. What are the territories of music? And in particular, what territories can only be negotiated through music?